Evaluación De Algunos Parámetros Productivos Y Sanitarios Del Hato De La Uan Sede Usme - Castellanos Peña, Juan Manuel (Universidad Antonio Nariño, 2022)
In this productive and reproductive analysis, it seeks to evaluate the activities that have been carried out during the last 18 months in the production of the dairy herd of the UAN headquarters Usme, to perform an analysis of the data obtained focused on milk production that is carried out cape. The information of the herd was collected, such as the inventory of animals, weight, age of females. in lactation and in the weighing of milk, the above compiled through the Ganadero ® software, evaluating the data of the animals in production, the information of interest was obtained productive and reproductive in the herd and with this information it is sought to contribute to improve health parameters and animal welfare.